Informal Cross-Border Trade in Africa: Operations, Policy, and Opportunities - Park, Jimin; Lim, Michael K.; Murali, Karthik (Management Science, 2024)
Informal cross-border trade (ICBT) refers to the illegal activities of cross-border commerce conducted by unregistered small-scale traders. We seek to develop insights to understand the ICBT value chain and offer policy recommendations to successfully integrate it into the formal economy. Using a game-theoretic model, we analyze the operations and key market dynamics of ICBT. We analyze the policy implications of three representative UN directives: enhancing marginalized traders’ access to formal channels, reducing export tax rates for formal traders, and introducing an alternative simplified trade regime (STR) for informal traders. All three policies result in an increase in government proceeds when the inherent profitability of the formal or STR channels is sufficiently high. Furthermore, social welfare increases when the policies effectively balance wholesale price competition within the formal and informal channels. We apply our model to a case study based on Uganda’s agricultural exports over an 11-year horizon. The access enhancement policy is most effective in increasing government proceeds but least effective in improving the welfare of other participants. The tax reduction policy enhances traders’ profitability but sacrifices the welfare of farmers and government proceeds substantially. Finally, the STR acknowledgement policy results in the largest increase in profitability of marginalized traders and farmers but comes at the cost of government proceeds. This paper was accepted by Jay Swaminathan, operations management. Funding: This work was supported by the Institute of Management Research, College of Business Administration, Seoul National University. Supplemental Material: The data and online appendix are available at https://doi.org/10.1287/mnsc.2022.02479 .